In Vitro Effect of Three-Antibiotic Combinations plus Potential Antibiofilm Agents against Biofilm-Producing Mycobacterium avium and Mycobacterium intracellulare Clinical Isolates - Sara Batista; Mariana Fernandez-Pittol; Lorena San Nicolás; Diego Martínez; Marc Rubio; Montserrat Garrigo; Jordi Vila; Griselda Tudó; Julian González-Martin (MDPI AG, 2023)
Patients with chronic pulmonary diseases infected by Mycobacterium avium complex (MAC) often develop complications and suffer from treatment failure due to biofilm formation. There is a lack of correlation between in vitro susceptibility tests and the treatment of clinical isolates producing biofilm. We performed susceptibility tests of 10 different three-drug combinations, including two recommended in the guidelines, in biofilm forms of eight MAC clinical isolates. Biofilm developed in the eight isolates following incubation of the inoculum for 3 weeks. Then, the biofilm was treated with three-drug combinations with and without the addition of potential antibiofilm agents (PAAs). Biofilm bactericidal concentrations (BBCs) were determined using the Vizion lector system. All selected drug combinations showed synergistic activity, reducing BBC values compared to those treated with single drugs, but BBC values remained high enough to treat patients. However, with the addition of PAAs, the BBCs steadily decreased, achieving similar values to the combinations in planktonic forms and showing synergistic activity in all the combinations and in both species. In conclusion, three-drug combinations with PAAs showed synergistic activity in biofilm forms of MAC isolates. Our results suggest the need for clinical studies introducing PAAs combined with antibiotics for the treatment of patients with pulmonary diseases infected by MAC.